Time-invariant entanglement and sudden death of nonlocality - Bi-Heng Liu; Xiao-Min Hu; Jiang-Shan Chen; Chao Zhang; Yun-Feng Huang; Chuan-Feng Li; Guang-Can Guo; Goktug Karpat; Felippe F. Fanchini; Jyrki Piilo; Sabrina Maniscalco (My University, 2025)
We investigate both theoretically and experimentally the dynamics of entanglement and nonlocality for two qubits immersed in a global pure dephasing environment. We demonstrate the existence of a class of states for which entanglement is forever frozen during the dynamics, even if the state of the system does evolve. At the same time nonlocal correlations, quantified by the violation of the Clauser-Horne-Shimony-Holt (CHSH) inequality, either undergo sudden death or are trapped during the dynamics.